Cluster scattering in the non-local model - Timofeyuk, N. K.; Gómez-Ramos, M. (Frontiers in Physics, 2023)
Scattering of weakly-bound nuclei with a pronounced cluster structure is strongly affected by their breakup. Usually, this mechanism is accounted for in a three-body model with pairwise potentials. The interaction potentials between complex systems are nonlocal due to the existence of excitation channels and antisymmetrization. However, a common practice is to use local optical potentials in cluster scattering studies. To assess the validity of replacing nonlocal optical potentials by their local equivalents we extend the local equivalent discretised coupled channel (LECDCC) approach proposed by us for deuteron scattering in [Phys. Rev. C98, 011601(R) (2018)] to the case of cluster scattering. We consider the case of $^6$Li+$^{120}$Sn at 27 and 60 MeV and compare the angular distributions and reaction cross sections for elastic and breakup cross sections with those obtained in standard CDCC with local equivalents of nonlocal potentials. We found that while elastic scattering is not significantly affected by nonlocality, the breakup observables could be affected by up to 20$%$ depending on kinematical conditions of their observation.